STRATEGI KOMUNIKASI PERSUASIF HUMAS WISATA BAHARI LAMONGAN UNTUK MENARIK MINAT WISATAWAN MELALUI INSTAGRAM @WISATABAHARILAMONGAN - Widya Ayu Kusumaningtyas; Ita Nurlita; Rini Ganefwati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2022)
Persuasive communication is one of the studies of communication that is often used to influence other people in various ways about what will be offered. The spread of the Covid-19 outbreak has had an impact on almost all sectors of life in Indonesia. One of the sectors that has experienced the most drastic impact from this pandemic besides the economic and health sectors is the tourism industry. Lamongan Marine Tourism is one of the tourist attractions affected by the pandemic. Currently, Marine Tourism Lamongan is incessantly carrying out various promotions to attract tourists to visit there. For this reason, it is necessary to provide tourist information media that is easily accessible and found in search engines by potential tourists. One of the social media that can be utilized is Instagram. This has been implemented by Wisata Bahari Lamongan Public Relations, which has an account with the name @wisatabaharilamongan. Wisata Bahari Lamongan focuses on persuasive tourism communication activities online by utilizing Instagram. In this study, researchers used a qualitative descriptive research method where data collection techniques were obtained through interviews, observation and documentation. The subjects in this study were the Wisata Bahari Lamongan Public Relations and the Instagram account @wisatabaharilamongan. The technique used in this study is the reward and order technique. The persuasive communication strategy implemented by Wisata Bahari Lamongan's public relations in attracting tourists through Instagram @wisatabaharilamongan is to prioritize existing facilities, provide promos for entrance tickets, giveaways, and special shows during holiday seasons. In this study, it was shown that there was an increase in sales feedback of around 40% -50%, this could be a reference that the persuasive communication was successful.